Increasing the Therapeutic Efficacy of Extracellular Vesicles From the Antigen-Specific Antibody and Light Chain Perspective - Nazimek, Katarzyna; Bryniarski, Krzysztof (Frontiers in Cell and Developmental Biology, 2021)
Due to their exceptional properties, extracellular vesicles (EVs) receive special attention as next generation biotherapeutics and vehicles for drug delivery. However, despite having many advantages over cell-based therapies, EVs usually exert lower therapeutic efficacy. This results from a number of hurdles that are faced by the EV-based approaches. Administered EVs could be rapidly cleared by the mononuclear phagocytes as well as can randomly distribute within various tissues, making tissue penetration and cell targeting insufficient. However, recent research findings imply that these limitations could be overcome with the use of antigen-specific antibodies and light chains. Major histocompatibility complex (MHC) class II-expressing EVs have been shown to form aggregates after co-incubation with antigen-specific antibodies, which greatly enhanced their biological efficacy. On the other hand, EVs could be coated with antibody light chains of chosen specificity to direct them towards desired target cell population. Both findings open up a promising perspective to achieve the highest efficacy of the EV-based approaches. Herein we discuss the opportunities for enhancing EV’s biological activity by using specific antibodies and light chains in the context of the challenges faced by such therapeutic approach.